Magnetic and electric antennas synergy for partial discharge measurements in gas-insulated substations: Power flow and reflection suppression. (January 2023) - Mier, Christian; Rodrigo Mor, Armando; Vaessen, Peter; Lathouwers, André
Graphical abstract: Highlights: Partial discharge pulse power flow measurements in gas-insulated substations. Reflections identification in GIS using electric and magnetic antennas. Partial discharge charge estimation using electric and magnetic sensors in GIS. Pulse overlapping reduction in gas-insulated substations. Abstract: One of the main difficulties in measuring partial discharges (PD) in gas-insulated substations (GIS) is the overlapping of pulses at the sensor's location, which distorts the pulse resolution and the charge estimation. This research presents a new method called "synergy, " which identifies and suppresses reflections using magnetic and electric antennas in the very-high frequency range. By scaling the antennas' outputs and adding them, it is possible to segregate forward and backward pulses. Additionally, by multiplying the electric and magnetic signals, the power flow of the pulses is obtained, which identifies the propagation direction and the location of discontinuities in the transmission path. The synergy method is evaluated in three scenarios: a fully matched test bench using a calibrated pulse, a full-scale GIS using a calibrated pulse, and a full-scale GIS using a PD defect. The results showed that the pulse reflections can be eliminated from the incident pulse, improving the charge calculation when the pulses overlap. The output of this research represents an improvement for PD monitoring in GIS, exhibiting a tool for better defect localization, pulse wave shape construction, charge estimation, and possible interference rejection. © 2017 Elsevier Inc. All rights reserved.